2013
DOI: 10.5267/j.msl.2013.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of job stress and emotional intelligence on job performance

Abstract: Researchers and scholars of management and behavioral sciences have tried to determine effective factors, which influence on efficiency and effectiveness in order to increase organization performance and they have tried to identify factors, which create job stress. In this research, we investigate the effect of job stress on job performance through emotional, organizational and moral intelligence. The study is a descriptive-analytic one, which is based on correlation, uses survey method to gather data and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…It is in line with the previous research conducted by [12] and [26] which shows that work stress does not have a negative influence on performance. This assumption is also supported by the fact that the field which causes it to happen according to several respondents is because they can overcome the sense of pressure or stress they experience.…”
Section: Effects Of Stress On Performancesupporting
confidence: 93%
“…It is in line with the previous research conducted by [12] and [26] which shows that work stress does not have a negative influence on performance. This assumption is also supported by the fact that the field which causes it to happen according to several respondents is because they can overcome the sense of pressure or stress they experience.…”
Section: Effects Of Stress On Performancesupporting
confidence: 93%
“…For example, Mikolajczak et al (2007) showed that, when confronted with emotional labor, high-trait EI individuals experience lower levels of burnout and somatic complaints. Similarly, Rafiee et al (2013) contended that the ability of employees to use their emotions and feelings, and also their ability to influence the feelings of other personnel, directly decreases physical and psychological stress in work situations. Chan (2006) found that emotional exhaustion was influenced by emotional 11 OCB and performance appraisal and positive regulation, while personal accomplishment was influenced by utilization of emotions in Chinese secondary school teachers.…”
Section: Mrr 381mentioning
confidence: 99%
“…The results indicated that while there was not any meaningful relationship between gender and job satisfaction there was some meaningful relationship between marital status and job satisfaction. Rafiee et al (2013) studied the effect of job stress on job performance through emotional, organizational and moral intelligence. They reported that job stress influenced on job performance through organizational intelligence and moral intelligence, but job stress did not impact on job performance through emotional intelligence.…”
Section: Introductionmentioning
confidence: 99%